LEADERSHIP, PROFESSIONAL COMPETENCE IN TEACHER PERFORMANCE: MOTIVATION AS A MEDIATING VARIABLE: Case Study of SMK KEDUNG JEPARA District - Irkhamul Azka Aditiya, Ahmad; Fu’ad, Eko Nur (Jurnal Bina Bangsa Ekonomika, 2025)
This study aims to determine the influence of Leadership Role, Professional Competence of Teachers and Motivation on Teacher Performance of SMK in Kedung District, Jepara Regency. The population of this study is vocational school teachers in Kedung District. From this population, the researcher took all samples using the saturated sample technique as many as 82 teachers. The data collection method uses a questionnaire. Furthermore, the analysis tool used by Smart PLS. The results of this study are that Leadership has no positive and insignificant influence on teacher performance, Leadership has a significant positive influence on motivation, Professional competence has a significant positive influence on teacher performance, Professional competence has a significant positive influence on motivation, Motivation does not have a significant positive influence on teacher performance, Leadership does not have an insignificant influence on teacher performance Along with motivation as a mediation variable, Professional competence does not have an insignificant influence on teacher performance along with motivation as a mediating variable